Neoradio – koniec radia jakie znamy? - Iwanicka, Agnieszka (Wydawnictwo Naukowe UAM, 2012)
In the text I am trying to trace the changes that occurred in the audio area in radio programming (radio format), ways of transmission (e.g. Internet radio), and formation new forms of expression (new forms of radio species). I’m trying to show what the radio has gained through adjusting to changes (e.g. programs targeting a speciﬁ c group, corecipients of the radio, more interactivity, the increasing number of ways to answer to the radio, new educational tools – podcasts) and what has been lost (freedom of language of radio presenters, poor quality software, disappearance of species of classic radio, lower technical quality Internet communications, Internet piracy). This combination will demonstrate how much this “blind” medium, once it opened up to the recipient and the changes that require new technologies, is mature and aware of its role as a new communications medium.
Neoradio – End of the Radio as We Know It?
Keywords: formatted radio; Internet radio; podcasting